Polyamide 6 single polymer composites (eXPRESS Polymer Letters, 2009)
Combining the two basic techniques used for the preparation of single polymer composites (SPCs), hot compaction and film stacking, a polyamide 6 (PA 6) single polymer composite was manufactured. The starting materials were PA 6 high tenacity yarn (reinforcement) and PA 6 film prepared via melt quenching (matrix), both expected to be the two principal polymorphic modifications of PA 6 and thus differing in their melting temperatures. The prepared single polymer composite is characterized by a layered structure and shows superior mechanical properties due to the good wetting – tensile modulus is improved by 200% and the ultimate tensile strength – by 300–400% as compared to the isotropic matrix film. Improvement of the interfacial adhesion via transreactions promoted by Sb2O3 as a catalyst was also undertaken.